(untitled) (Innovative professional education, 2023)
The current state of the economy is characterized by significant changes in the labor market. New trends – the rapid development of innovations and technologies, the emergence of new specialties at the intersection of several industries, the need for saving and efficient use of energy resources, the spread of new forms and types of employment, increased competition, increased migration, the possibility of constantly changing the place of work and profession - put forward new requirements for ownership knowledge, skills and abilities. Soft universal interprofessional skills (soft skills), such as knowledge and information management, self-organization, negotiation, the ability to analyze and make effective decisions, solve complex problems, allow a person to quickly adapt to new conditions, together with specialized specialized knowledge – allow to gain competitiveness and demand in the labor market. Such specialized knowledge today are qualifications in the energy efficiency and energy saving sector.